Communication from the executive of the Commonwealth, transmitting a communication from Hon. L.P. Walker, Secretary of War, in relation to the time of service of the volunteer forces of Virginia (LLMC-digital (Series), 1861)
Governor John Letcher's July 1, 1861 letter regarding the included June 29, 1861 communication from L.P. Walker, Secretary of War of the Confederate States. He requested that Virginia change its muster policy for volunteers from twelve months to three years.